Laminar non-Newtonian impinging jet flow confined by sloping plane walls - A. S. Cavadas (2012)
An experimental investigation was carried out to characterize the flow field in a liquid impinging jet confined by inclined plane walls at an angle of 12 degrees relative to the plate and emanating from a rectangular duct for two non-Newtonian fluids and a Newtonian reference fluid. The nozzle-to-plate distance (D) was kept constant at DIH = 0.8. The experiments were complemented by a numerical investigation for purely viscous generalized Newtonian fluids. Detailed measurements of mean flow fields were carried out by laser-Doppler anemometry at inlet duct Reynolds numbers of 200 pertaining to laminar flow regime and all flow fields were found to be symmetric relative to the x-y and x-z center planes. The two non-Newtonian fluids were aqueous solutions of xanthan gum (XG) and polyacrylamide (PAA) at weight concentrations of 0.2% and 0.125% respectively. A characteristic three-dimensional helical flow was seen to exist inside the recirculation, starting at the symmetry plane and spiraling to the flat side walls, which eliminated the separated flow region near these side walls, as previously found for Newtonian fluids 151. Upon reaching the flat side wall region, the fluid in helical motion exits the recirculation and joins the main flow stream creating near-wall jets which were enhanced by the non-Newtonian fluid nature. The PAA solution, which was more elastic than the XG solution, was found to be subject to larger decelerations than the XG solution in the vicinity of the impinging plate. The numerical simulations investigated the roles of shear-thinning and inertia on the main flow characteristics for purely viscous fluids at Reynolds numbers between 10 and 800. The length of the recirculation (L-R) is constant in the central portion of the channel and decays to zero before reaching the flat side walls. At high Reynolds numbers a slight increase in L-R at the edge of the core of the flow is apparent. As expected, inertia increases the length of the recirculation as for Newtonian fluids, but somewhat surprisingly it also increases the three-dimensional nature of the flow by reducing the extent of the central core. Shearthinning enhances the role of inertia especially at high Reynolds numbers, whereas at low Reynolds numbers the opposite behavior is observed.